Vector competence of Swedish Culex pipiens mosquitoes for Japanese encephalitis virus - Krambrich, J.; Akaberi, D.; Lindahl, Johanna F.; Lundkvist, Å.; Hesson, J.C. (Springer, 2024)
Background: Japanese encephalitis virus (JEV) is an emerging mosquito-borne Orthoflavivirus that poses a significant public health risk in many temperate and tropical regions in Asia. Since the climate in some endemic countries is similar to temperate climates observed in Europe, understanding the role of specific mosquito species in the transmission of JEV is essential for predicting and effectively controlling the potential for the introduction and establishment of JEV in Europe.